SYSTEMIC APPROACHES REGARDING THE DEVELOPMENT OF PERSONIFIED «NEW LEARNING» - Giacomuzzi, S.; Garber, K.; Velasquez-Montiel, S.; Ausserer, O. (Психологія та особистість, 2021)
The new learning requires first an accompanied implementation. Already after one year, it becomes apparent that the corresponding grade levels and performance curves of the students can be improved. Moreover, the participants agree that intraindividual learning definitely improves. In addition, the implementation of the project can greatly increase the well- being of the pupils at school, which naturally has an effect on their performance. We live in an ever faster changing world, in which the school concepts of previous years should be revised and optimized. New approaches, like gender sensitive designs are necessary to continue the new learning project’s success. «New learning» is basically an individualized learning style. «New learning» starts by the individual itself. The individual is the basis for conditions, learning contents, rhythm, duration and intensity of the teaching. The appropriate slogan is: know the individual’s baseline conditions, so you start building from his/her foundations. The systemic side of this measure is the integration of the elements in a dynamic whole that feels right to teachers, parents as well as the main targets: The students. A substantial modification of the usual class structure is a central feature of the program. Modules of individual knowledge are essential for the teaching strategy. In the context of the modular structure there are rather learning fields and subjects. Different fields of learning (basic curriculum and electives) form another basis of the program, flanked by common living rooms and leisure programs as well as practical courses. Learning fields are understood as a basis of general culture and subjects as their specializations. The individual programming (IPP) is organized in basis blocks which are constantly adapted. All experiences and goals are described in individual portfolios. Tutorial settings are provided for continuously evaluation and support. A total of two classes were enrolled in the program (27 high school pupils). The program took place in northern Italy (South Tyrol). Pupil age ranged from 15a +/- 1 SD. After the first academic year pupil satisfaction scores amounted to 75% regarding obtained achievements. 90% of all parents showed a high satisfaction score and wanted to have the program continued. Teacher consent for the program reached up to 76%. However, teachers a 33% increase in their workload. Over 70% of the pupils wished a continuation of the project. Student achievement increased up to 6%. Study difficulties reduced to approximately 40%.